Effectively Screening for Coronary Artery Disease in Patients Undergoing Orthotopic Liver Transplant Evaluation - Bryan C. Lee; Feng Li; Adam J. Hanje; Khalid Mumtaz; Konstantinos D. Boudoulas; Scott M. Lilly (Journal of Transplantation)
Coronary artery disease (CAD) is prevalent in patients with end-stage liver disease and associated with poor outcomes when undergoing orthotopic liver transplantation (OLT); however, noninvasive screening for CAD in this population is less sensitive. In an attempt to identify redundancy, we reviewed our experience among patients undergoing CAD screening as part of their OLT evaluation between May 2009 and February 2014. Demographic, clinical, and procedural characteristics were analyzed. Of the total number of screened patients (n=132), initial screening was more common via stress testing (n=100; 75.8%) than coronary angiography (n=32; 24.2%). Most with initial stress testing underwent angiography (n=52; 39.4%). Among those undergoing angiography, CAD was common (n=31; 23.5%). Across the entire cohort the number of traditional risk factors was linearly associated with CAD, and those with two or more risk factors were found to have CAD by angiography 50% of the time (OR 1.92; CI 1.07–3.44, p=0.026). Our data supports that CAD is prevalent among pre-OLT patients, especially among those with 2 or more risk factors. Moreover, we identified a lack of uniformity in practice and the need for evidence-based and standardized screening protocols.